Efektifitas Mediasi dalam Sengketa Wanprestasi Pembelian Elektronik: Studi Kasus Barang Cacat - Mariatul Camilia; Indah Nabila; Irbatul Bahirah (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Direct (offline) purchase transactions are still the choice of the public, especially to ensure the physical condition of the goods. However, in direct purchases of electronic goods (offline) in physical stores, disputes often arise when the purchased goods are defective or damaged after several days of use. Cases like this are a form of default by the seller. One alternative dispute resolution that can be used is mediation, which is a settlement process with the help of a neutral third party to reach a mutual agreement. In this case, an analysis of the effectiveness of mediation was carried out in resolving default disputes related to defective goods in electronic purchases in physical stores. Using case studies and qualitative approaches, it was found that mediation is effective if both parties have good intentions and are willing to communicate openly. Mediation can accelerate dispute resolution without having to go through a long and expensive legal process.